Timely referral and safe transport of neonates admitted to neonatal intensive care unit of tertiary care government hospital of Agra district: a cross sectional study - Negi, Rudresh; Agrawal, Renu; Kaushal, Sunil K.; Misra, Sunil K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Timely referral and safe transport form a crucial link for the survival and safety of sick newborn. Thus the study aimed at assessing referral and transport of sick neonates admitted to NICU of a tertiary care government hospital and the factors associated with direct referral and safe final transport. Methods: A hospital based cross-sectional study was carried out in among 450 neonates and was based on face to face interview with caregivers. The data was analyzed using proportions and mean values Chi square test of significance and independent t test were appropriately applied and p<0.05 was taken to be statistically significant. Odds ratios were calculated for dichotomous variables. Results: 72.6% of high risk pregnancies were transferred timely in utero to district hospitals. Around two thirds (65.8%) of neonates were referred by doctors. Treatment during transportation was administered to 29.6% of the neonates. 50.2% of neonates have used the services of an ambulance at some point of time during their travel. Highly significant association of direct referral was observed with earlier age at admission (2.3 days), early development of neonatal symptoms (1.45 days), lesser gestational age (33.1 weeks) and lesser total distance travelled (15.7 km). The odds of final transport of newborns in ambulance was significantly more in males (OR=1.5), rural residents (OR=1.5) and registered pregnancies (OR=4.3). Conclusions: Wide variations remain in neonatal referral and transport with some glaring gaps which need to be adequately addressed.